El Anticipo del Impuesto a la Renta es Contradictorio, Inconstitucional y Afecta a la Economía del Contribuyente - Angamarca Figueroa, Aldo Bolívar (2016)
This research has been conducted focused on the relevant problems of our current outlook both government and economic. The advance payment of income tax has been implemented by the State in order to fund public spending failed to observe that directly violent Supreme Standard legal system. The problem arises when making a charge by the administration to taxpayers, first; unborn obligation or operative event, second; violating the express provision in Article 165 paragraph 1 of the Constitution, which provides that only you can raise taxes in advance in state of emergency. It has been observed in a relevant way that in our country the advance income tax has affected the economy of taxpayers and competitiveness with foreign industry because it represents a limitation for our industry. With this figure advance payment is restricting the expansion and the rise of the Ecuadorian industry as due to the recovery of advance income tax it performed based on the previous fiscal year, and in this way also arises the problem because any fiscal year is equal; one year may be other benefits and maybe not, is why during the tour of our project can explain and accurately determine the fundamentals of unconstitutionality, contradiction and impact on the economy.